Effects of Adding Ваtсinеl-К® Probiotic and Vaccine CEVAC SET-K® on Some Biochemical Markers of Broilers Parents’ Stock - Al-Aqaby, Aamer; Hammod, Mohanad; Alsadwi, Akhil; A Hammadi, Hassan; A Glaskovich, Aleftina; A Krasochko, Petr (The Iraqi Journal of Veterinary Medicine, 2025)
The combined use of probiotics and vaccines offers a potential strategy to enhance poultry health and reduce dependence on antibiotics. However, the metabolic impact of such interactions in broiler breeder chickens remains insufficiently explored. This study aimed to evaluate the effects of Batcinel‑К® (Bacillus subtilis BIM‑B 454 D) and the inactivated Salmonella vaccine CEVAC SET‑K® on lipid profile, carbohydrate metabolism, renal indices, and mineral status in broiler breeder chickens. Three hundred Ross 308 chicks were distributed into six equal groups: control (no treatment), probiotic only, vaccine only, and three combined probiotic + vaccine regimens: Regimen A (four probiotic cycles 1–35 days + vaccination at 42 and 98 days + booster probiotic 91–98 days), Regimen B (four probiotic cycles 1–35 days + recurrent 3-day probiotic dosing 42–91 days + vaccination 42 and 98 days), and Regimen C (two probiotic cycles 1–21 days + intermittent 2-day probiotic dosing 42–91 days + single vaccination 98 days). Serum collected at 56, 63, and 112 days was analyzed for total cholesterol, triglycerides, glucose, uric acid, creatinine, calcium, phosphorus, and magnesium. At 112 days, Regimen A produced a significant decline in total cholesterol and triglycerides (P < 0.05), accompanied by reduced uric acid and creatinine at 63–112 days. Glucose concentrations increased significantly in all probiotic groups, while magnesium was elevated in Regimen A at 112 days. Supplementation with Batcinel‑К® particularly when applied under Regimen A in combination with CEVAC SET-K®, improved lipid metabolism and mineral status in broiler breeders. Structured probiotic–vaccine programs may therefore enhance metabolic resilience and overall flock performance‎‎‎.